The Role of Religious Commitment, Collectivism, and Long-Term Orientation in Consumer Impulse Buying - Awisal Fasyni (Universitas Prasetiya Mulya, 2023)
This study examines religion and culture’s influence on impulsive and compulsive buying. The research population is people who have made impulsive and compulsive purchases for fashion products, with a sample size of 212 respondents. Questionnaires were distributed through social media, and the collected data were analyzed using PLS. The study results show that 1) religious commitment negatively affects compulsive buying, 2) collectivism culture has been shown to positively affect impulsive and compulsive buying, 3) religious commitment is not proven to affect impulse buying, and 4) long-term orientation has also been shown not to affect impulsive and compulsive buying. Businesses can encourage impulse and compulsive buying by focusing their target market on collectivists with low levels of religious commitment.